A potent immunotoxin targeting fibroblast activation protein for treatment of breast cancer in mice. Issue 4 (14th September 2015) - Fang, Jinxu; Xiao, Liang; Joo, Kye‐Il; Liu, Yarong; Zhang, Chupei; Liu, Shuanglong; Conti, Peter S.; Li, Zibo; Wang, Pin
Abstract : Fibroblast activation protein (FAP) is highly expressed in the tumor‐associated fibroblasts (TAFs) of most human epithelial cancers. FAP plays a critical role in tumorigenesis and cancer progression, which makes it a promising target for novel anticancer therapy. However, mere abrogation of FAP enzymatic activity by small molecules is not very effective in inhibiting tumor growth. In this study, we have evaluated a novel immune‐based approach to specifically deplete FAP‐expressing TAFs in a mouse 4T1 metastatic breast cancer model. Depletion of FAP‐positive stromal cells by FAP‐targeting immunotoxin αFAP‐PE38 altered levels of various growth factors, cytokines, chemokines and matrix metalloproteinases, decreased the recruitment of tumor‐infiltrating immune cells in the tumor microenvironment and suppressed tumor growth. In addition, combined treatment with αFAP‐PE38 and paclitaxel potently inhibited tumor growth in vivo . Our findings highlight the potential use of immunotoxin αFAP‐PE38 to deplete FAP‐expressing TAFs and thus provide a rationale for the use of this immunotoxin in cancer therapy. Abstract : What's new? As a key component of tumor stroma, tumor‐associated fibroblasts (TAFs) promote malignant growth, angiogenesis, invasion, and metastasis. Fibroblast activation protein (FAP), a surface protein that is exceedingly expressed in TAFs, could function as an attractive target for cancer therapy in a broad range of cancers. In this study, the authors developed a novel immunotoxin αFAP‐PE38 targeting the nonmalignant compartment of solid tumors and demonstrated its potent antitumor activity as well as the enhanced therapeutic efficacy of this immunotoxin with paclitaxel. These studies pave the way for applying the combination of FAP‐targeting immunotoxin and chemotherapeutic agent as a promising new strategy to enhance clinical application of immunotoxin‐based therapies.